NILAI KEARIFAN LOKAL BALI DALAM MATERI PEMBELAJARAN BAHASA BALI DI SMA KELAS X SE-KOTA SINGARAJA - Sukma Wirani, Ida Ayu; Purnami, Ida Ayu Putu (Prasi: Jurnal Bahasa, Seni, dan Pengajarannya, 2014)
This study was conducted to determine the language learning materials Bali containing the values of local wisdom and to know the types of local wisdom contained in Balinese language learning material in high school Class X in Singaraja. This study used a qualitative descriptive analysis, the results of this study indicate that the material in the book that is used in Bali to discuss learning in high school Class X in Singaraja basically about four language skills. The fourth aspect of the language skills developed in the collection of material that is as discourse, basic vocabulary, and Crete bases. Of whole language learning material in Bali, local moral values exist in the material discourse. Through discourse material that contains the values of local wisdom will provide extensive knowledge, imparting of knowledge, broaden your horizons, and transform values in students, so it can be said that the values of local wisdom in Balinese language learning materials related to values education character in Balinese language discourse material. Key words: local moral values, character education, language learning materials Bali.